Phylogenomic Analyses of Bradyrhizobium Reveal Uneven Distribution of the Lateral and Subpolar Flagellar Systems, Which Extends to Rhizobiales - Garrido-Sanz, Daniel (2019)
Dual flagellar systems have been described in several bacterial genera, but the extent of their prevalence has not been fully explored. Bradyrhizobium diazoefficiens USDA 110T possesses two flagellar systems, the subpolar and the lateral flagella. The lateral flagellum of Bradyrhizobium displays no obvious role, since its performance is explained by cooperation with the subpolar flagellum. In contrast, the lateral flagellum is the only type of flagella present in the related Rhizobiaceae family. In this work, we have analyzed the phylogeny of the Bradyrhizobium genus by means of Genome-to-Genome Blast Distance Phylogeny (GBDP) and Average Nucleotide Identity (ANI) comparisons of 128 genomes and divided it into 13 phylogenomic groups. While all the Bradyrhizobium genomes encode the subpolar flagellum, none of them encodes only the lateral flagellum. The simultaneous presence of both flagella is exclusive of the B. japonicum phylogenomic group. Additionally, 292 Rhizobiales order genomes were analyzed and both flagellar systems are present together in only nine genera. Phylogenetic analysis of 150 representative Rhizobiales genomes revealed an uneven distribution of these flagellar systems. While genomes within and close to the Rhizobiaceae family only possess the lateral flagellum, the subpolar flagellum is exclusive of more early-diverging families, where certain genera also present both flagella.